N-heteroacenes and N-heteroarenes as N-nanocarbon segments - Bunz, Uwe H. F.; Freudenberg, Jan (Accounts of chemical research, 2019)
Conspectus N-Heteroacenes and N-heteroarenes are the heterocyclic congeners of the acenes and arenes, in which one or several perimeter C-H bonds have been substituted by pyridine-type nitrogen atoms. They are formally segments out of N-doped nanographenes. Position and number of the nitrogens vary greatly, making N-heteroacenes and N-heteroarenes define a vast class of N-nanographene segments; they display modular electronic and structural properties. The nitrogen atoms in the perimeter lead to finely tunable frontier molecular orbital positions and therefore improved electron affinity and higher oxidative stability but conversely also require and allow different synthetic approaches than those reported for the synthesis of their hydrocarbon and nanographene analogues. The chemistry of N-heteroarenes, despite being known for more than a century, has made significant progress in the last years and established these materials both as powerful n-channel semiconductors in thin film transistors and as useful emitters in organic light emitting diodes (OLEDs) and in photovoltaic devices. The electronegative nitrogen atoms impart a deep LUMO into the azaacenes and azaarenes, improve electron injection, and enable powerful electron transport but also charge separation in bulk-heterojunction type organic photovoltaic (OPV) devices. At the same time, azaacenes and azaarenes are fundamentally exciting materials that push the limits of structure and stability, constantly displaying novel topologies and structures as variations of a simple leitmotif; we expect a bright future for esthetically pleasing yet highly functional N-heterocyclic species.Firstly, we discuss novel structures and structural elements that have evolved during the last years in N-heteroacene and N-heteroarene chemistry and delineate their properties. An important aspect is the oligomerization or better multimerization of azaacene and azaarene units into novel and surprising topologies, in which multiple azaarenes or azaacenes are stitched together. Examples are tetrahedral assemblies of tetraazapentacenes but also cyclic tetramers of different types of azaacenes and linearly bent, S-shaped, formally dimeric species. An exciting aspect of the exploration of the structural manifold of azaacenes is their electronic interaction in such assemblies and their solid-state microstructure. A further aspect of this work is the increase in size of the azaacenes and concepts that allow stabilization of the larger congeners. The attachment of four benzo units to the azaacene core is a powerful concept that stabilizes tetraazaheptacenes and should also be useful to achieve persistent tetraazanonacenes.Secondly, we describe the success of N-heteroacenes and N-heteroarenes in organic electronic devices; specifically, the use of symmetrical halogenated tetraazapentacenes as superb n-channel transistor materials with air stable and persistent radical anions as charge carriers; we discuss the structural reason for their success. Use of azaacenes and azaarenes is not restricted to transistors, but they are also applied in bulk heterojunction photovoltaic devices and in brightly emitting OLEDs.Azaacenes and azaarenes are attractive segments out of hetero-nanographenes and objects of study, starting from fundamental structural and topological questions, ranging to powerful applications in organic electronics. The general interest in azaacenes is witnessed by the constantly increasing number of groups who discover and work on these materials as novel functional and flexible species.